Strategi Komunikasi Extinction Rebellion Indonesia dalam Mendorong Kesadaran Krisis Iklim melalui Instagram - Debtian, Muhammad Rizky; Venus, Anter; Rahmawan, Detta (Jurnal Media dan Komunikasi Indonesia, 2026)
This study aims to analyze how Extinction Rebellion Indonesia (XR Indonesia) designs and implements its communication strategy on Instagram to promote public awareness of the climate crisis. The object of this research is XR Indonesia’s Instagram-based activism, with data collected through in-depth interviews with internal members and followers, as well as content observation and document analysis conducted between June and November 2024. Using a qualitative case study approach, the data were analyzed through an interactive model of data reduction, display, and conclusion drawing. The findings indicate that XR Indonesia’s communication practices align structurally with Oepen’s environmental communication strategy framework (assessment, planning, production, and action-reflection) yet are adapted to the decentralized and volunteer-based nature of digital activism. Assessment and evaluation processes are largely informal and reflective rather than systematically documented. Integrating Fisher’s narrative paradigm and Moody-Adams’ concept of narrative activism, XR’s communication operates as a counter-narrative strategy that constructs moral claims, collective identity, and systemic critiques in the digital arena. In conclusion, XR Indonesia demonstrates that adaptive narrative-based communication can function as a strategic tool in digital environmental activism, despite limitations in formal evaluation and audience measurement.